Dispersion pattern and sampling of Diaphorina citri Kuwayama (Hemiptera:Psylidae) populations on Citrus suhuiensis hort. ex tanaka in Padang Ipoh Terengganu, Malaysia - Sule, Hassan; Muhamad, Rita; Omar, Dzolkhifli; Hee, Alvin Kah Wei; Chik, Zazali (Universiti Putra Malaysia Press, 2012)
An understanding of the dispersion patterns of a pest is an important pre-requisite for developing an effective pest management program. In this study, fifty five (55) citrus trees were surveyed for adult Diaphorina citri once every four week for a period of ten months (March 2011 – December 2011). Analysis of spatial-distribution pattern using various indices of dispersion and regression models showed that D. citri exhibited an aggregated distribution on Citrus suhuiensis. Taylor’s power law ( a = 0.897, b = 1.267, R2 = 0.74) fitted the data better than Iwoa’s regression modal (a = 0.376, ß = 0.196, R2 = 0.409). The optimal sample sizes needed for fixed precision levels of 0.10, 0.15 and 0.25 were estimated using Taylor’s regression coefficients, and the required sample sizes increased dramatically with increased levels of precision. Therefore, these sampling-plan presented should serve as a tool for an efficient estimation of D. citri population density in citrus orchard for pest management decision.